The effect of increased part-charges on the health-seeking behaviours of Group 3 workers and their families : a thesis presented in partial fulfilment of the requirements for the degree of Master in Arts (social policy) at Massey University - Haas, M. Beth (Massey University, 1995)
This thesis is about health, change and user charges. In 1991 New Zealand embarked in a new direction for the funding of health services, including extensive use of a targeting regime in which 'those that can afford' social services were paying more so that those who could not were paying less. For the 'high-income' families classified as Group 3, this meant that part charges at point of service were increased at all levels of health services. Concerns immediately arose that the income levels had been set too low and would create financial barriers for some 'high-income' families, particularly those on the margin. This thesis explores the demand response of 129 families in Group 3 to the new charges imposed by the Interim Targeting Regime. The survey population is characterised by high incomes and insurance coverage across income levels. Through a nonrandom survey methodology based on the opinions and perceptions of the user community (Group 3 workers and their families), over one-quarter of the survey families reported health services demand being diverted from allopathic medical services. However, even though 25% reported demand diversion, only 11% of families reporting lowered health status. The study also looked at diversion from conventional medicine to alternatives including self-treatment, seeking advice from a chemist, complementary therapies or changing lifestyle habits. The data did not suggest diversion to alternatives equal to the reduction of conventional medical services. Through the use of nonparametric statistical techniques, characteristics of the survey population were analysed in an attempt to begin untangling a complex web of factors affecting the survey population's health services demand when faced with increases in price. Factors included in this study were income level, insurance coverage, health status, gender, family size and composition . Various subsamples of the survey population reported different effects and different magnitudes of demand diversion. The differences between insured and uninsured families were particularly marked. Evidence provided by the user community implicates a high degree of moral hazard within the insured subsample. The study suggests further research on the influence on moral hazard in meeting the stated goals of the reforms. Because the study is nonrandom and exploratory, any claim of representativeness would be unwarranted. However, the study suggests that the attributes of high incomes and insurance coverage may be inherent to Group 3. To more accurately assess the representativeness of any research on the effects of the increase in part charges on Group 3, the study proposes a further clarification of the specific attributes of the families belonging in the Group 3 category is necessary. Finally, the study questions the adequacy of the targeting regime and the increase in part charges for meeting the objectives set out by the health reformers, particularly in respect to the objectives of cost containment and individuals becoming more responsible for their own health.
Keywords: New Zealand; User charges; Medical care -- Utilization